Tristetraprolin promotes survival of mammary progenitor cells by restraining TNFα levels - Stedile, Micaela; Lara Montero, Angela; García Solá, Martín Emilio; Goddio, María Victoria; Beckerman, Inés; Bogni, Emilia; Ayre, Marina; Naguila, Zaira; Coso, Omar A.; Kordon, Edith C. (Frontiers in Cell and Developmental Biology, 2024)
Tristetraprolin (TTP) is an RNA binding protein that destabilizes mRNAs of factors involved in proliferation, invasiveness, and inflammation. Disruption of the gene that codes for TTP (Zfp36) led to severe arthritis, autoimmunity, cachexia and dermatitis in mice. It has been shown that these phenotypes were mostly due to excessive TNF levels in the affected tissues. We have previously reported that TTP expression is required for lactation maintenance. Our results indicated that conditional MG TTP-KO female mice displayed early involution due to the untimely induction of pro-inflammatory pathways led mostly by TNF overexpression. Here we show that reducing TTP levels not only affects the fully differentiated mammary gland, but also harms morphogenesis of this tissue by impairing the progenitor cell population. We found that Zfp36 expression is linked to mammary stemness in human and mice. In addition, diminishing TTP expression and activity induced apoptosis of stem-like mouse mammary cells, reduced its ability to form mammospheres in culture and to develop into complete glands when implanted into cleared mammary fat pads in vivo. Our results show that survival of the stem-like cells is compromised by increased levels of inflammatory cytokines and stimulation of signaling cascades involving NFB, STAT3 and MAPK-p38 activation. Moreover, TNF overexpression and the consequent p38 phosphorylation would be the leading cause of progenitor cell death upon TTP expression restriction. Taken together, our results reveal the relevance of TTP for the maintenance of the mammary progenitor cell compartment by maintaining local TNF levels at bay.